Consumer Dispute Resolution Through The Al-Shulh Channel From The Perspective Of Sharia Economic Law - Rika Tulzanna; Siti Annisa Br. Nainggolan; Muhammad Nur Iqbal (Sean Institute, 2024)
Study This aiming For analyze about settlement dispute through Al- Shulh route or peace . Research This aiming For give understanding deep about phenomenon certain without do research field . Al- Shulh or Shulh in a way Language means peace , decide quarrel or dispute . Research This use method study bibliography , namely research conducted​ with method researching ingredients library . Data sources used includes secondary data like compilation law sharia economy , results research , and the views of scholars. Research results show that Al- Shulh can help the parties concerned in finish problem with peaceful and transparent without harm one​ the parties concerned . Al- Shulh assist the parties concerned​ with easy and efficient . Inside Islamic law , Al- Shulh is form permissible agreement​ in frame tie a individual and also group . Al- Shulh can concluded that Al- Shulh or Shulh is a business For reconcile two parties who are at odds , quarreling , each other revenge and hostility in maintain rights . With carry out Al- Shulh expected the end dispute said . Al- Shulh or agreement peace between​ man is one of religious advice , and a judge may For convey recommendation or advice to the disputing parties​ For willing do compromise and make peace , but No may until to form coercion , pressure or almost pressure​ approach form Requirement . Analysis This done For understand How Al- Shulh concept or peace functioning in sharia economy , as well as For give solution in finish dispute in a way peace in accordance with Islamic religious advice.